Tuberculosis in wild pigs from Argentina - Barandiaran, Soledad; Marfil, Maria Jimena; La Sala, Luciano Francisco; Tammone, Agostina; Condori, Walter Ezequiel; Winter, Marina; Abate, Sergio Damián; Rosas, Ana Carolina; Ponce, Loredana; Carpinetti, Bruno Nicolás; Serena, Maria Soledad; Lozano Calderon, Laura Camila; et al. (Springer, 2024)
Mycobacterium bovis, a member of the Mycobacterium tuberculosis complex (MTC) and non-tuberculous Mycobacteria (NTM), may infect wild and domestic mammals, including humans. Although cattle are the main hosts and spreaders of M. bovis, many wildlife hosts play an important role worldwide. In Argentina, wild boar and domestic pigs are considered important links in mammalian tuberculosis (mTB) transmission. The aim of this work was to investigate the presence of M. bovis in wild pigs from different regions of Argentina, to characterize isolates of M. bovis obtained, and to compare those with other previously found in vertebrate hosts. A total of 311 samples from wild pigs were obtained, and bacteriological culture, molecular identification and genotyping were performed, obtaining 63 isolates (34 MTC and 29 NTM). Twelve M. bovis spoligotypes were detected. Our findings suggest that wild pigs have a prominent role as reservoirs of mTB in Argentina, based on an estimated prevalence of 11.2 ± 1.8% (95% CI 8.0–14.8) for MTC and the frequency distribution of spoligotypes shared by cattle (75%), domestic pigs (58%) and wildlife (50%). Argentina has a typical scenario where cattle and pigs are farm-raised extensively, sharing the environment with wildlife, creating conditions for effective transmission of mTB in the wildlife–livestock–human interface.